2007
DOI: 10.1523/jneurosci.1709-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gating and Recruitment of P/Q-, N-, and R-Type Ca2+Channels in Hippocampal Mossy Fiber Boutons

Abstract: Voltage-gated Ca 2ϩ channels in presynaptic terminals initiate the Ca 2ϩ inflow necessary for transmitter release. At a variety of synapses, multiple Ca 2ϩ channel subtypes are involved in synaptic transmission and plasticity. However, it is unknown whether presynaptic Ca 2ϩ channels differ in gating properties and whether they are differentially activated by action potentials or subthreshold voltage signals. We examined Ca 2ϩ channels in hippocampal mossy fiber boutons (MFBs) by presynaptic recording, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
204
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(226 citation statements)
references
References 54 publications
18
204
4
Order By: Relevance
“…In many central synapses, Ca V 2.1 channels are preferentially located at the release sites and are more effectively coupled to neurotransmitter release than other Ca 2+ channel types (Li et al 2007, Matsushita et al 2002, Qian and Noebels 2001, 2000, Dunlap et al 1995, Mintz et al 1995, Wu et al 1999, Iwasaki et al 2000. At these synapses, the action potential-evoked Ca 2+ influx and the local Ca 2+ increase that triggers neurotransmitter release are mainly determined by the kinetics of opening and closing, the open probability and the unitary conductance of Ca V 2.1 channels (Borst and Sakmann 1998, Sabatini and Regehr 1999, Meinrenken et al 2002, 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many central synapses, Ca V 2.1 channels are preferentially located at the release sites and are more effectively coupled to neurotransmitter release than other Ca 2+ channel types (Li et al 2007, Matsushita et al 2002, Qian and Noebels 2001, 2000, Dunlap et al 1995, Mintz et al 1995, Wu et al 1999, Iwasaki et al 2000. At these synapses, the action potential-evoked Ca 2+ influx and the local Ca 2+ increase that triggers neurotransmitter release are mainly determined by the kinetics of opening and closing, the open probability and the unitary conductance of Ca V 2.1 channels (Borst and Sakmann 1998, Sabatini and Regehr 1999, Meinrenken et al 2002, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…They play a prominent role in initiating action-potential-evoked neurotransmitter release both at peripheral neuromuscular junctions and central synapses, mainly within the cerebellum, brainstem, and cerebral cortex (Katz et al 1996, Catterall 1998, Iwasaki et al 2000. Even when pharmacological and electrophysiological studies in brain slices from rodents have revealed that P/Q-, N-and R-type channels cooperate in controlling release at many central excitatory synapses, P/Q-type channels have a dominant role, partly because of their more efficient coupling to the exocytotic machinery (González Inchauspe et al 2004, Li et al 2007, Matsushita et al 2002, Qian and Noebels 2001, 2000, Wu et al 1999, Mintz et al 1995.…”
Section: C1 Cav21 (P/q-type) Calcium Channelsmentioning
confidence: 99%
“…First, BCs exclusively use P/Q-type Ca 2ϩ channels to initiate transmitter release (6). Because P/Q-type Ca 2ϩ channels activate and deactivate very rapidly (42), this specialization will contribute to the high speed of synaptic transmission. Second, Ca 2ϩ channels and Ca 2ϩ sensors of exocytosis are tightly coupled at BC output synapses, leading to a fast and temporally precise local Ca 2ϩ transient at the sensor (7).…”
Section: Discussionmentioning
confidence: 99%
“…How is this summation achieved? Propagation of APs to MF boutons triggers the opening of P/Q-, N-, and R-type voltage-gated calcium channels (VGCCs) (Castillo et al, 1996;Breustedt et al, 2003;Pelkey et al, 2006), with P/Q-type VGCCs contributing the major fraction of intrabouton calcium elevations (Pelkey et al, 2006;Li et al, 2007). Activity-dependent broadening of APs will increase the total presynaptic calcium through the recruitment of additional VGCCs and their prolonged opening (Geiger and Jonas, 2000).…”
Section: Calcium Dynamics Gates Mf-ca3 Short-term Facilitationmentioning
confidence: 99%